Pengendalian Persediaan Bahan Baku Pada Industri Tenun Ikat “Medali Mas” Kediri - M Ayub Ardhirakmanto; Sri Rahayuningsih; Ana Komari (Universitas Kadiri, 2020)
Tenun Ikat Medali Mas Industry has long been producing woven cloth in various models and patterns. Problems faced by researchers regarding the supply of raw materials, due to the absence of controlling the amount of inventory of raw materials needed specifically, while the company is faced with demand uncertainty which is very influential on the procurement of raw material supplies. So the holding of research with forecasting methods to calculate the needs in one production period. The variable in this research is about controlling raw material inventory. The first is to collect raw material needs data. Perform forecasting with the Exponential smoothing method α = 0.15, and Moving average N = 2. Next, the forecast results determine the smallest error value with indicators MAD, MSE, and MAPE. After the chosen method will be used as a reference for forecasting in the next period. Then perform efficient safety stock and reorder point calculations for one production period. From the results of calculations on the raw material yarn produces Maximum Inventory = 4287 kg; Safety Stock = 53 kg; Reorder Point = 128 kg while on the raw material paint Maximum Inventory = 304 kg; Safety Stock = 7 kg; Reorder Point = 12 kg.Industri Tenun Ikat Medali Mas sudah lama memproduksi kain tenun dalam berbagai model maupun corak. Permasalahan yang dihadapi oleh peneliti mengenai persediaan bahan baku, dikarenakan belum adanya pengendalian jumlah persediaan bahan baku yang dibutuhkan secara spesifik, sedangkan perusahaan dihadapkan pada ketidakpastian permintaan yang sangat berpengaruh pada pengadaan persediaan bahan baku. Sehingga diadakannya penelitian dengan metode forecasting untuk memperhitungkan kebutuhan dalam satu periode produksi. Variabel dalam penelitian ini tentang pengendalian persediaan bahan baku. Pertama dilakukan pengumpulan data kebutuhan bahn baku. Melakukan peramalan dengan metode Exponential smoothing α = 0,15, dan Moving average N = 2. Berikutnya dari hasil peramalan ditentukan nilai eror terkecil dengan indikator MAD, MSE, dan MAPE. Setelah metode terpilih nantinya akan dijadikan acuan untuk melakukan peramalan pada periode selanjutnya. Kemudian melakukan perhitungan safety stock dan reorder point yang efisien untuk satu periode produksi. Dari hasil perhitungan pada bahan baku benang menghasilkan Maximum Inventory = 4287 kg; Safety Stock = 53 kg; Reorder Point = 128 kg sedangkan pada bahan baku cat Maximum Inventory = 304 kg; Safety Stock = 7 kg; Reorder Point = 12 kg.